L'effectivité des jugements en droit administratif canadien et québécois - Garant, Patrice (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
Enforcement of court judgments against government and public authorities at all levels has never been studied. It raises two main concerns. First, what is the legal regime for compulsory execution of judgments ? A distinction must be made between situations where the legality of an act or omission is challenged with success by a citizen and situations where the Administration is held to pay a sum of money in civil matters (tort, contract, property). Second, when government officials and administrators agree to comply with court judgments, is their willingness to comply genuinely effective ? Are there means of nullifying the real impact of judgments ?